2014
DOI: 10.1186/1742-2094-11-97
|View full text |Cite
|
Sign up to set email alerts
|

miR-155 induction in microglial cells suppresses Japanese encephalitis virus replication and negatively modulates innate immune responses

Abstract: BackgroundMicroglial cells, which are resident macrophages of the central nervous system, play important roles in immune responses and pathogenesis. Japanese encephalitis virus (JEV) is a neurotropic virus that infects microglial cells in brain. Several microRNAs including miR-155 and miR-146a play an important role in defining the microglia inflammatory profile. In this study, we have investigated the effect of miR-155 and miR-146a modulation on JEV infection as well as innate immune responses in human microg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
93
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(104 citation statements)
references
References 47 publications
(64 reference statements)
5
93
1
3
Order By: Relevance
“…Thus, in this study, we aimed to address the role of miRNA-regulated pathways in the JEV-induced neuroinflammation model. Recently, the roles of miR-29b and miR-155 in microglial activation during JEV-induced neuroinflammation were studied (42,53,54). In this study, we demonstrated that miR-15b is stimulated both in vitro and in vivo, and miR-15b regulates the inflammatory response following JEV infection by targeting RNF125.…”
Section: Discussionmentioning
confidence: 72%
“…Thus, in this study, we aimed to address the role of miRNA-regulated pathways in the JEV-induced neuroinflammation model. Recently, the roles of miR-29b and miR-155 in microglial activation during JEV-induced neuroinflammation were studied (42,53,54). In this study, we demonstrated that miR-15b is stimulated both in vitro and in vivo, and miR-15b regulates the inflammatory response following JEV infection by targeting RNF125.…”
Section: Discussionmentioning
confidence: 72%
“…Distinct types of miRNAs may affect innate immunity, and specifically miR-146a is shown to be a negative regulator of TLR signaling, which could be of importance in neurodegenerative diseases [114]. Another miRNA, miR-155, may affect the complement system by attenuating FH in a human cell model of Japanese encephalitis [115]. Lastly, the complement system may affect miRNAs.…”
Section: Crosstalk Between Complement the Tlrs And Other Systems Relmentioning
confidence: 98%
“…In human microglial CHME3 cells, infection with the neurotropic flavivirus Japanese encephalitis virus (JEV) resulted in the up-regulation of miR-155 [53]. Nevertheless, miR-155 over-expression was associated to a restriction in JEV replication, a significant reduction in JEV-induced IFN-b and an attenuation of the expression of complement factor H (CFH), a negative regulator of complement activation, and interferon regulatory factor 8 (IRF8), an IFN-b inducer.…”
Section: Mir-155 and Other Virusesmentioning
confidence: 99%